Feasibility of Aerobic Exercise in the Subacute Phase of Recovery From Traumatic Brain Injury: A Case Series. Issue 4 (October 2018) - Morris, Timothy P.; Costa-Miserachs, David; Rodriguez-Rajo, Pablo; Finestres, Jordi; Bernabeu, Montserrat; Gomes-Osman, Joyce; Pascual-Leone, Alvaro; Tormos-Muñoz, Jose Maria
Abstract : Background and Purpose: Aerobic exercise is as important for individuals with traumatic brain injury (TBI) as for the general population; however, the approach to aerobic training may require some adaptation. The objective of the trial program was to examine the feasibility of introducing aerobic physical exercise programs into the subacute phase of multidisciplinary rehabilitation from moderate to severe TBI, which includes computerized cognitive training. Case Description: Five individuals undergoing inpatient rehabilitation with moderate or severe TBIs who also have concomitant physical injuries. All of these individuals were in the subacute phase of recovery from TBIs. Intervention: An 8-week progressive aerobic physical exercise program. Participants were monitored to ensure that they could both adhere to and tolerate the exercise program. In addition to the physical exercise, individuals were undergoing their standard rehabilitation procedures that included cognitive training. Neuropsychological testing was performed to gain an understanding of each individual's cognitive function. Outcomes: Participants adhered to both aerobic exercise and cognitive training. Poor correlations were noted between heart rate reserve and ratings of perceived effort. Two minor adverse events were reported. Discussion: Despite concomitant physical injuries and cognitive impairments, progressive aerobic exercise programs seem feasible and well tolerated in subacute rehabilitation from moderate to severe TBI. Findings highlight the difficulty in measuring exercise intensity in this population. Video Abstract available for more insights from the authors (see Video, Supplemental Digital Content 1, available at:http://links.lww.com/JNPT/A235 ) Abstract : Supplemental Digital Content is Available in the Text.